Recovering Unlawful Advantages in the Context of EU State Aid Tax Ruling Investigations - Pieter Van Cleynenbreugel (Market and Competition Law Review)
The European Commission has recently begun focus increasingly on the compatibility of Member States’ tax ruling procedures with EU State aid law. In that respect, it has ordered the recovery of unlawfully granted advantages through those procedures. This article examines to what extent the application of EU law principles of legitimate expectations and legal certainty are to take stock in State aid recovery proceedings of this particular legal certainty-enhancing and legitimate expectations creating tax ruling context. It additionally questions whether recovery in this particular context should be tailored to the specific national ruling framework having resulted in the advantage granted in violation of Article 107 TFEU.